ANALISIS INCREASE TAX DAN TAX AMNESTY TERHADAP TAX ASSURANCE DALAM PROBABILITAS PEMERIKSAAN PAJAK - Angelina, Natalia; Kurniawan, Rudy; Haryono, Haryono (Journal of Information System, Applied, Management, Accounting and Research, 2024)
Charge is a required commitment owed by people or substances. In this context, the SAMSAT office participates in public services, contributing to fiscal monitoring and supervision of tax amnesty implementation. It was found that individuals tend to disagree more than agree with tax amnesty, but tax amnesty tends to improve tax compliance. The research method used was qualitative, involving interview sessions at the SAMSAT office. The goal was to gather detailed information about various aspects of public services, with the main objective of providing constructive suggestions to enhance service standards. Interviews were conducted at the Samsat UPT Wilayah I Kota Pontianak, covering the overall profile and structure of the institution, as well as documents related to tax regulations. The research results indicate that increased taxes impact tax assurance, affecting both expenditures and central taxes. Tax rates in daily collections are subject to change, and tax assurance plays a crucial role in handling and overseeing local taxpayers. The government ensures compliance with existing tax regulations, monitored by the Regional Revenue Agency and the State Audit Board, with annual routines to engage the general public in a timely manner.